Principles of traditional Malay house spatial planing as vertical modern dwelling design concept - Misnat, Nordin; Mohd Tahir, Mazlan; Abd Aziz, Mohamed Nizam; Ahmad, Norfazillah (2025)
The quality of houses should be appropriate for their role, manner of life, culture, and economy. The Malays' living space reflects their personalities and is founded on the Islamic religion in accordance with Syariah. Comfort, safety, health, tranquility and aesthetic factors all contribute to the well-being of the inner space, resulting in a blessed house. Today's homes cannot respond properly to the needs of their occupants and are heavily impacted by the west. It is opposed to the needs of the local design community, particularly the Malays. In comparison to the design of traditional Malay house (TMH) architecture, this concept and architectural approach have met many factors in attaining its objectives. The findings will be the basis for addressing the main issues and to recommend the application of the conceptual Malay heritage design in the design towards the creation of quality interior design dwelling as design concept toward cultural-tradition resilient.